Numerical Study of Natural Convection Heat Loss from Cylindrical Solar Cavity Receivers. (23rd January 2014) - Prakash, M.
Abstract : The numerical study of the natural convection loss occurring from cylindrical solar cavity receivers is reported in this communication. These cavity receivers can be used with solar dish concentrators for process heat applications at medium temperature levels. Three cylindrical cavity receivers of diameter 0.2, 0.3, and 0.4 m with aspect ratio equal to one and opening ratios of 1 and 0.5 are used for the analysis. Fluent CFD software is used for the analysis of the three-dimensional (3D) receiver models. In this study the receiver tubes within the cylindrical cavity are modeled as a helical coil similar to those existing in actual systems. The flow of the working fluid within the helical coil is also modeled. The simulations are performed for fluid inlet temperatures of 150°C and 250°C and for receiver inclination angles of 0 (sideways-facing cavity), 30, 45, 60, and 90 degree (vertically downward-facing receiver). It is found that the convective loss increases with increasing mean fluid temperature and decreases with, increase in receiver inclination. The convective loss is found to increase with, opening ratio. These observations are true for all cavity receivers analysed here. A Nusselt number correlation involving Rayleigh numbers, receiver inclinations, and opening ratios is proposed for the convective loss.